Implementation of the hidden curriculum in the formation of the religious character of students - Ulfa Fitria; Nur Khalimah (Curricula)
The educational curriculum applied in Islamic boarding schools to educate students' character is limited to using a written curriculum system and a hidden curriculum applied in teaching activities at Islamic boarding schools. This study aims to explain the hidden curriculum policy (hidden curriculum in the Darussalam Blokagung Banyuwangi Islamic boarding school). This study uses a qualitative descriptive method, which emphasizes field observation. This method aims to obtain complete and in-depth information by collecting data through observations, interviews, and documentation. As a result of this study, the researcher found that the hidden curriculum applied at the Darussalam Blokagung Islamic boarding school has been implemented since the founders of the Islamic boarding school, namely KH. Mukhtar Syafa'at Abdul Ghofur. The hidden curriculum implemented includes congregational prayers, madrasah diniyah, istighosah, study sessions of the Ihya’ Ulumiddin book, Quran learning using the Yanbu’a method, monthly Ahad Legi gatherings, and weekly ro’an activities every Friday. This research contributes to uncovering the role of the hidden curriculum as an effective strategy for character development in Islamic boarding schools. It provides a reference for other educational institutions to integrate similar practices into their teaching systems.